The security of freedom : essays on Canada's anti-terrorism bill - Macklem, Patrick; Roach, Kent, 1961-; Daniels, Ronald J. (Ronald Joel), 1959- (University of Toronto Press, 2001)
Canada's Anti-Terrorism Bill (Bill C-36) proposes legislative changes to combat potential threats to Canada's security from terrorism at home and abroad. The papers in this collection address concerns about the scope and ramifications of these changes.